An experimental study of the effect of back rake angle in rock cutting - Rostamsowlat, I.; Richard, Thomas; Evans, Brian (Pergamon, 2018)
The objective of this paper is to investigate the influence of the rake angle on the magnitude of the intrinsic specific energy and the inclination of the force acting on the cutting face of a Polycrystalline Diamond Compact (PDC) sharp cutter while tracing a groove on the surface of a rock sample. An extensive and comprehensive set of cutting experiments was performed on a wide range of quarry rock samples using a state of the art rock cutting equipment (Wombat). The results conform with the previous studies by other researchers; the intrinsic specific energy is in good agreement with the uni-axial compressive strength of the rock samples when the cutter is positioned at back rake angles between 5° to 20°. New results on a few rock samples were also obtained by performing novel experimental tests at very large rake angles (θ > 70°) as well as negative rake angles, showing that the intrinsic specific energy increases dramatically once the back rake angle exceeds 75°. Results also indicate that the decrease of the apparent interfacial friction angle with increasing back rake angle seems to follow a “universal trend” weakly dependent on the rock sample.